Focal Cerebral Arteriopathy of Childhood: Novel Severity Score and Natural History. Issue 11 (November 2018) - Fullerton, Heather J.; Stence, Nicholas; Hills, Nancy K.; Jiang, Bin; Amlie-Lefond, Catherine; Bernard, Timothy J.; Friedman, Neil R.; Ichord, Rebecca; Mackay, Mark T.; Rafay, Mubeen F.; Chabrier, Stéphane; Steinlin, Maja; et al.
Abstract : Background and Purpose—: Focal cerebral arteriopathy (FCA)—a common cause of arterial ischemic stroke in previously healthy children—often progresses over days to weeks, increasing the risk of recurrent stroke. We developed a novel severity scoring system designed to quantify FCA progression and correlate with clinical outcomes. Methods—: The VIPS study (Vascular Effects of Infection in Pediatric Stroke) prospectively enrolled 355 children with arterial ischemic stroke (2010–2014), including 41 with centrally confirmed FCA. Two neuroradiologists independently reviewed FCA cerebrovascular imaging, assigning a graded severity score of zero (no involvement) to 4 (occlusion) to individual arterial segments. The FCA severity score (FCASS) was the unweighted sum. In an iterative process, we modeled scores derived from different combinations of arterial segments to identify the model that optimized correlation with clinical outcome, simplicity, and reliability. Results—: The optimal FCASS summed scores from 5 arterial segments: supraclinoid internal carotid artery, A1, A2, M1, and M2. The median (interquartile range) baseline FCASS was 4 (2–6). Of 33 children with follow-up imaging, the maximum FCASS (at any time point) was 7 (5–9). Twenty-four (73%) had FCA progression on follow-up with their maximum FCASS at a median of 8 (5–35.5) days poststroke; their median FCASS increase was 4 (2.5–6). FCASS did not correlate with recurrent arterial ischemic stroke. Maximum (but not baseline) FCASS correlated with 1-year pediatric stroke outcome measures ( P =0.037). Conclusions—: Our novel scoring system for FCA severity correlates with neurological outcomes in the VIPS cohort and provides a tool for FCA treatment trials under development. Abstract : Supplemental Digital Content is available in the text.